Can We Improve the Monitoring of People With Multiple Sclerosis Using Simple Tools, Data Sharing, and Patient Engagement? - Allen-Philbey, Kimberley; Middleton, Rod; Tuite-Dalton, Katie; Baker, Elaine; Stennett, Andrea; Albor, Christo; Schmierer, Klaus (Frontiers in Neurology, 2020)
Technological innovation is transforming traditional clinical practice, enabling people with multiple sclerosis (pwMS) to contribute healthcare outcome data remotely between clinic visits. In both relapsing and progressive forms of multiple sclerosis (MS), patients may experience variable disability accrual and symptoms throughout their disease course. The potential impact on the quality of life (QoL) in pwMS and their families and carers is profound. The introduction of treatment targets, such as NEDA (no evidence of disease activity) and NEPAD (no evidence of progression or active disease), that guide clinical decision-making, highlight the importance of utilising sensitive instruments to measure and track disease activity and progression. However, the gold standard neurological disability tool - expanded disability severity scale (EDSS) - has universally recognised limitations. With strides made in our understanding of MS pathophysiology and DMT responsiveness, maintaining the status quo of measuring disability progression is no longer the recommended option. Outside the clinical trial setting, a comprehensive monitoring system has not been robustly established for pwMS. A 21st century approach is required to integrate clinical, paraclinical and patient reported outcome (PRO) data from electronic health records, local databases and patient registries. Patient and public involvement (PPI) is critical in the design and implementation of this workflow. To take full advantage of the potential of digital technology in the monitoring and care, and QoL of pwMS will require iterative feedback between pwMS, healthcare professionals (HCP), scientists and digital experts.